Proteksi konsumen dalam dagang dengan sistem elektronik - Faris, Muhammad (Maliki Interdisciplinary Journal, 2024)
In Indonesia, technological developments are increasingly advanced, such as the existence of a trading system through electronic transactions. Transactions like this require a legal protection to consumers, because the parties involved do not meet in person but online. This paper shows that transactions must arise disputes and will provide explanations and protection for consumers who do it. There are also those who show that this transaction cannot be implemented optimally because of the law that requires implementing regulations. In Law Number 8 of 1999 concerning Consumer Protection has not been able to control protection in this transaction, especially in terms of differences in jurisdiction to the parties. In disputes that arise from consumers, related parties can do so through court channels and other channels, namely outside the court according to the agreement of the parties concerned, as for other ways, namely online. In this paper, it is better for the government to immediately make regulations on electronic trading systems and dispute resolution.